Did Regulation Fair Disclosure affect credit markets? - Li, Yutao; Saunders, Anthony; Shao, Pei (Journal of Banking & Finance, 2015)
This study assesses whether the implementation of Regulation Fair Disclosure (Reg FD) has affected the quantity and quality of information in credit markets. We find that, after Reg FD, borrowing from new lenders was associated with a higher loan spread. We also document that, after Reg FD, (1) borrowers became more dependent on relationship lending; (2) lead lenders retained a higher loan share; and (3) a typical loan syndicate involved a smaller number of participating lenders. We interpret these results as evidence of an increased level of information asymmetry in credit markets after Reg FD.